Kolaborasi Strategis Perpustakaan: Studi Kasus pada Perpustakaan Institut Teknologi Sepuluh Nopember - Kurniasari, Meinia Prasyesti; Rizqita, Talitha Jasmine; Aini, Malikah Qurrota; Mukaromah, Nisaul (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research examines the strategies implemented by ITS libraries in realizing collaboration and facing collaboration challenges using the Saunders and Corning (2020) model. Data were collected through observation and interviews with two informants who have crucial roles in the ITS library. Data analysis techniques were carried out inductively, starting with transcribing interview results into text, followed by a coding process to identify emerging themes, and thematic analysis to organize data based on the main themes. In planning, ITS libraries adhere to the SOP for cooperation and select partners who are professional, communicative, and have integrity. Intensive coordination is carried out before decisions are made, followed by the signing of the MoU. An example of a project is involving a publisher to support the writing of lecturers' textbooks. Top management support and professional partners are key to success. Evaluation is done through positive impact reports, such as increased access to academic resources. Challenges include lack of professionalism of partners and communication stagnation with institutional management. Supporting factors include strong leadership, ITS branding, and strategic policies, making the library a center of continuous innovation. Overall, the findings show that ITS Libraries have successfully executed collaboration projects by following a systematic framework.